Analytical study of micropolar fluid flow and heat transfer in a channel with permeable walls - Fakour, M.; Vahabzadeh, A.; Ganji, D.D.; Hatami, M. (Journal of molecular liquids, 2015)
In this study, micropolar fluid flow in a channel subject to a chemical reaction is investigated analytically using least square method (LSM) and numerically. Some efforts are done to show reliability and performance of the present method compared with the numerical method (Runge–Kutta fourth-order) to solve this problem. The results reveal that the LSM can achieve suitable results in predicting the solution of these problems. Also, the effect of consequential parameters such as Reynolds number (Re), micro rotation and Peclet number on the stream function, velocity and temperature distribution is discussed. The results show that the stream function decreases with increase of Reynolds number and velocity boundary layer thickness decreases as Re increases. With increase of Peclet number (Pe) the oscillation of temperature fluid and concentration profile increases. Furthermore, the effect of the Reynolds and Peclet numbers on Nusselt and Sherwood numbers is completely investigated from the physical view point in the present study. •The stream function decreases with increase of Reynolds number and velocity boundary layer thickness decreases as Re increases.•With increase of Peclet number (Pe) the oscillation of temperature fluid and concentration profile increases.•Also Increase in Reynolds number leads to increase in Nusselt number but the value of Nusselt number decrease with increase of Peclet number.